البحرية الطرابلسية وحرب البحر المتوسط (Comprehensive Journal of Science, 2025)
The Tripolitanian naval power is considered one of the important characteristics of the Eyalet of Tripoli, which had its resonance and prestige in the Mediterranean Sea. The Pashas of the Eyalet succeeded in developing it into a formidable naval force. This force was not a product of the period under study, but rather began with the formation of the Eyalet. There were several reasons behind its emergence as a dominant power in the Mediterranean during the modern era, specifically the Karamanli period (1711–1835 AD). During this era, the Eyalet of Tripoli was able to take the lead in this activity. What gave it this advantage was its geographical location overlooking the Mediterranean Sea, on the one hand, and its connection—that is, the Mediterranean Sea—to the commercial mediation between Africa and Europe, on the other.The Karamanlis came to Tripoli during the reign of Dragut Pasha, and their grandfather settled in the city of Tripoli, where he owned a garden in the Manshiyya suburb and resided there. He then married one of the Arab Tripolitanian women. This intermarriage led to the assimilation and integration of the Karamanlis within the indigenous population. This family was able to assume many important leadership positions, such as the Emirate of the Knights and the position of Pasha Agha, all the way to ruling the Eyalet of Tripoli (Firo, p. 32).This study focuses on the Tripolitanian naval power and its role during this period, its relationship with the other naval powers in the Mediterranean, including, but not limited to, the American Navy, as well as the armed conflict that occurred during this stage.The study will rely on a number of references that cover the study period and its various aspects.